Proses Adaptasi Mahasiswa Perantau Pasca Pembelajaran Daring ke Luring - Utama Sundayana; Yulianti (Bandung Conference Series: Public Relations, 2024)
Abstract. Culture shock in an individual occurs because a person enters a new culture to himself which makes him have to adjust to an environment, place, and habits that are different from his previous life. Students of Communication Science at the Islamic University of Bandung class of 2021 experience Culture Shock towards changes in learning from online to offline. This change affects the adaptation of overseas students, because they have to adjust to a new environment, language, and culture. The 2021 batch of Communication Science students at the Islamic University of Bandung experienced crocodile shock because they had to overcome anxiety and anxiety in direct social interaction. The purpose of this research is to examine the adaptation process of overseas students of the Faculty of Communication Science, Islamic University of Bandung class of 2021 after experiencing changes from online to offline learning. The research method in this study uses a qualitative method with a case study approach using the theory of culture shock from Samovar (2010). Then, data sources are obtained through interviews, observation, and documentation with Communication Science Students of the Islamic University of Bandung class of 2021. Data analysis will be carried out using data reduction analysis techniques, data presentation, and conclusion drawing. The results showed that in the adaptation process, overseas students felt several phases such as Honeymoon Phase, Crisis Phase, Adjusment Phase to Adaptation Phase. Culture shock barriers arise from several internal and external factors such as external factors in the form of environmental changes, to internal in the form of differences in perceptions and habits. The reasons for culture shock are differences in language, culture, habits, perceptions, communication and relationships that they felt were foreign before. Abstrak. Mahasiswa perantau Ilmu Komunikasi Universitas Islam Bandung angkatan 2021 mengalami perubahan pembelajaran dari daring ke luring. Namun, terdapat beberapa mahasiswa perantau angkatan 2021 tidak terbiasa dengan kegiatan tersebut sehingga hal tersebut menimbulkan gegar budaya. Masalah yang terjadi terhadap mahasiswa tersebut yakni adanya kesulitan dalam bersosialisasi dan berkomunikasi pada kegiatan tatap muka di lingkungan kampus yang seharusnya mereka sudah terbiasa dengan keadaan tersebut. Perubahan ini mempengaruhi adaptasi mahasiswa perantau, karena mereka harus menyesuaikan dengan lingkungan baru, bahasa, dan budaya. Mahasiswa perantau Ilmu Komunikasi Universitas Islam Bandung angkatan 2021 mengalami gegar budaya karena harus mengatasi rasa cemas dan gelisah dalam berinteraksi sosial atau berkomunikasi secara langsung. Tujuan penelitian ini dilakukan untuk mengkaji proses adaptasi mahasiswa perantau Fakultas Ilmu Komunikasi Universitas Islam Bandung angkatan 2021 setelah mengalami perubahan dari pembelajaran dari daring ke luring. Metode penelitian dalam penelitian ini menggunakan metode kualitatif pendekatan studi kasus dengan menggunakan tahapan gegar budaya. Kemudian, sumber data diperoleh melalui wawancara, observasi, serta dokumentasi dengan Mahasiswa Ilmu Komunikasi Universitas Islam Bandung angkatan 2021. Data analisa yang akan dilakukan dengan menggunakan teknik analisis reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa dalam proses adaptasinya mahasiswa perantau merasakan beberapa fase seperti Honeymoon Phase, Crisis Phase, Adjusment Phase hingga Adaptation Phase. Hambatan gegar budaya muncul dari beberapa faktor internal maupun external seperti faktor external berupa perubahan lingkungan, hingga internal berupa perbedaan persepsi dan kebiasaan. Alasan terjadinya gegar budaya adalah perbedaan bahasa, budaya, dan pergaulan yang mereka rasa asing sebelumnya.